2020
DOI: 10.1021/acs.jpcc.0c02180
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Both Tilting and In-Plane Molecular Rotational Angles for Dinaphtho[2,3-b:2′,3′-f]thieno[3,2-b]thiophene Using Near-Edge X-ray Absorption Fine Structure

Abstract: We demonstrate that both in-plane molecular rotational and tilting angles of the molecular orientation can be determined using the σ* resonance of sulfur (S) K-edge near-edge X-ray absorption fine structure. We examined dinaphtho­[2,3-b:2′,3′-f]­thieno­[3,2-b]­thiophene (DNTT) thin films on silicon dioxide (SiO2) and copper oxide (CuO x ) substrates which are relevant to the cost-effective organic field-effect transistors. In-plane directed transition moments were attributed to the electron excitation from S 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The first peak at 2473 eV and the second peak at 2475 eV were attributed to the electron excitation from S 1s core-shell to the largely overlapped σ* orbital related to the C-S bonding at the tienotiophene site. 33) The intensity of the first and second peaks showed the incident angle dependence. As the incident angle increases, the first peak showed an increasing tendency, whereas the second peak exhibited a decreasing one.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The first peak at 2473 eV and the second peak at 2475 eV were attributed to the electron excitation from S 1s core-shell to the largely overlapped σ* orbital related to the C-S bonding at the tienotiophene site. 33) The intensity of the first and second peaks showed the incident angle dependence. As the incident angle increases, the first peak showed an increasing tendency, whereas the second peak exhibited a decreasing one.…”
Section: Resultsmentioning
confidence: 98%
“…The analysis method has been explained in detail elsewhere. 33) In brief, the polarization dependence of the transition intensity has been analyzed to determine the molecular orientation of the tilting angle (β) and the in-plane rotational angle (Φ M ) in DNTT thin films. The definition of β and Φ M is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[ 6 ] Iwasawa et al also reported that the first layer of DNTT on SiO 2 was in an upright configuration, as determined by NEXAFS analysis. [ 7 ] Shioya et al reported that high‐resolution X‐ray diffraction (HR‐XRD) measurements revealed compression of the a‐ and b‐lattice constants and the existence of a thin‐film phase. [ 4 ] They emphasized that a more detailed study of the structure of the initial layers of DNTT is needed.…”
Section: Introductionmentioning
confidence: 99%
“…Their group reports that this instability is closely related to the degradation of device performances and that the encapsulation techniques effectively suppress the degradation [6]. Iwasawa et al also reported that the first layer of DNTT on SiO2 is in the upright configuration investigated by the NEXAFS analysis [7]. Shiroya et al investigated that high-resolution x-ray diffraction (HR-XRD) measurement revealed the compression of the a-and b-lattice constants and the existence of a thin film phase [4].…”
Section: Introductionmentioning
confidence: 99%